2010
DOI: 10.4049/jimmunol.1000549
|View full text |Cite|
|
Sign up to set email alerts
|

In Vivo Analysis of Ifn-γ1 and Ifn-γ2 Signaling in Zebrafish

Abstract: The zebrafish genome contains a large number of genes encoding potential cytokine receptor genes as judged by homology to mammalian receptors. The sequences are too divergent to allow unambiguous assignments of all receptors to specific cytokines, and only a few have been assigned functions by functional studies. Among receptors for class II helical cytokines—i.e., IFNs that include virus-induced Ifns (Ifn-ϕ) and type II Ifns (Ifn-γ), together with Il-10 and its related cytokines (Il-20, Il-22, and Il-26)—only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 45 publications
2
64
0
1
Order By: Relevance
“…Danio rerio IL-10R1 (also known as crfb7) has previously been shown to have no overt role in development or in the signal transduction for Danio rerio phi and gamma interferons (1,31). Our data confirm that IL-10R1 is functional during embryonic development in response to its cognate ligand, causing an increase in leukocytes.…”
Section: Resultssupporting
confidence: 70%
“…Danio rerio IL-10R1 (also known as crfb7) has previously been shown to have no overt role in development or in the signal transduction for Danio rerio phi and gamma interferons (1,31). Our data confirm that IL-10R1 is functional during embryonic development in response to its cognate ligand, causing an increase in leukocytes.…”
Section: Resultssupporting
confidence: 70%
“…For instance, crfb17, a necessary component of IFN-g receptor complexes in zebrafish, was upregulated by 6.35-fold. 43 We also identified obvious upregulation of 2 interferon regulatory factor (IRF) family members, irf1b (2.92-fold) and irf9 (2.15-fold) ( Figure 6D). …”
Section: Dysregulated Transcriptome In Zebrafish Myelopoiesis By Delementioning
confidence: 92%
“…For overexpression, the coding regions of DrIFNu1, DrIFNc1, DrIFNc2 were inserted into the restriction sites Xho I/Xba I of pCS2+ vector (Promega) to make zebrafish IFN expression plasmid (Aggad et al, 2009(Aggad et al, , 2010. Similarly, other plasmids including DrIFNu2, DrIFNu3, DrIFNu4 were made by insertion of their coding regions into Xho I/Xba I sites of pCS2+ vector (Promega).…”
Section: Plasmidsmentioning
confidence: 99%
“…Two types of fish IFN genes have been identified (Zou and Secombes, 2011). For example, zebrafish Danio rerio genome has four IFNu genes (IFNu1/2/3/4, or named IFN1/2/ 3/4) (Aggad et al, 2009;Altmann et al, 2003) and two IFNc genes (IFNc1/2) (Aggad et al, 2010;Igawa et al, 2006). Although the former of zebrafish IFNs use distinct receptors from mammalian type I IFNs (Aggad et al, 2009), crystal structure analyses have revealed that they are evolutionarily closer to mammalian type I IFNs than to type III IFNs (Hamming et al, 2011).…”
Section: Introductionmentioning
confidence: 99%